(untitled) (Journal of Misan Researches, 2024)
This study is concerned with showing some of the suggestive indications for the addition of the word "ibad" (servants) in the Holy Qur’an. When reading this word in the holy verses, we found that it was added to the apparent names, and it is added to two names only, namely ("Allah" and “Alrahman" (the Most Merciful). The study aims at explaining the reasons behind the addition of the word "ibad" to these names only and what meaning they convey that the Qur’anic text seeks to draw attention to. In some other verses, this word is added to some attached pronouns like (Na (1st person plural) - Ya (1st person singular) - Kaf (2nd person singular)- Haa (3rd person singular). It is found that each pronoun has its connotations that are specific to it. The first part of this study is devoted to talk about the indications of the addition of "ibad" to the apparent noun, while the second part will talk about the indications of its addition to the pronouns.